Effectiveness of 3Rs Waste Management Practice: Implications for Climate Change and Environmental Sustainability - Geoffrey Ukala; Chinweokwu Ukamaka Ukala; Nsimeneabasi Michael Udoh; Josephine Ese Konyeme; Folasade Oluyemisi Olayinka (Journal of Research in Environmental and Science Education, 2026)
The study examined the effectiveness of the 3Rs (Reduce, Recycle, and Reuse) waste management practice: Implications for climate change and environmental sustainability. A descriptive design (survey) was employed, while five research questions guided this research and were conducted in the University of Nigeria, Nsukka. Participants comprised all 333 undergraduate biology education students enrolled during the 2023/2024 academic session. All were purposively sampled to take part in the study as the population was deemed manageable. The questionnaire on Waste Management (QWM) served as a data collection tool. The questionnaire was duly validated by three professionals in science education and was trial tested on 20 students in the same institution, but different faculty, and yielded a reliability coefficient value of 0.81, using Cronbach’s alpha. Descriptive statistics of percentage, mean, and standard deviation were used to answer the study’s questions. The findings show that most practice waste management includes open dumping and burning composting, while the 3Rs were found to be rarely practiced in schools. The findings revealed that students are aware of the 3Rs approach to waste management. Among the prominent barriers identified were the school curriculum’s silence on 3Rs, lack of incentives to attract students to bring their waste for recycling, and the distance between dumpsites and where the populace lives. Lastly, the enforcement of environmental sanitation day within the school, the dumpsite should be located at a reasonable distance, and the opening of more dumpsite/waste containers within the schools was encouraged. It was recommended that an awareness program or campaign should be organized to enlighten the populace on the importance of the 3R approach to waste management.